The Effect Of Problem Based Solving Strategy Towards Students’ Speaking Skill - Terasne Terasne; Tri Setianingsih (Jurnal Paedagogy, 2020)
This research was aimed to find out the effect of Problem Based Solving (PBS) Strategy toward students’ speaking skill at SMPN 4 Praya Barat Daya. The kind of this research was a Quasi-experimental research. The samples divided into two classes were: experimental group consist of 27 students and control group consist of 27 students. They were chosen by using Cluster Random sampling technique. The method was non-equivalent control group design. The technique of data collection used pre-test and post-test. The instrument to get students’ score by oral test in the form of speaking test. Then the data was obtained by using t-test formula, The data was analyzed through descriptive analysis and inferential statistic, it shows that value of t-test was 2.409, the mean score of experimental group 86.96 and the mean score of control group was 58.81.Than t-test was higher than t-table with significant level was 0.05 (1.675) with DF was 52. It can be concludes that the used Problem Solving has positive effect towards students’ speaking skill at SMPN 4 Praya Barat Daya , it means the alternative hypothesis was accepted.